DNA Methylation at the DAT Promoter and Risk for Psychopathology: Intergenerational Transmission between School-Age Youths and Their Parents in a Community Sample - Cimino, Silvia; Cerniglia, Luca; Ballarotto, Giulia; Marzilli, Eleonora; Pascale, Esterina; D’Addario, Claudio; Adriani, Walter; Tambelli, Renata (Frontiers in Psychiatry, 2018)
Background: The effect of gene polymorphisms and promoter methylation, associated with maladaptive developmental outcomes, vary depending on environmental factors (e.g. parental psychopathology). Most studies have focused on 0-5 year-old children, adolescents or adults, whereas there is dearth of research on school-age youths and pre-adolescents. Methods: In a sample of 21 families recruited at schools, we addressed parents’ psychopathological symptoms (through SCL-90-R); offspring emotional-behavioral functioning (through CBCL-6-18); Dopamine Transporter gene (DAT1) for epigenetic status of the 5’-UTR and for genotype, i.e. VNTR polymorphism at the 3’-UTR. Possible associations were explored between bio-genetic and psychological characteristics within the same individual and between triplets of children, mothers, fathers. Results: DAT methylation of CpG at positions M1, M6 and M7 in mothers was correlated with maternal (Phobic) Anxiety, whereas in fathers’ position M6 was related to paternal Depression, Anxiety, Hostility, Psychoticism and higher Global-Severity-Index. No significant correlations were found between maternal and offspring DAT methylation. Significant correlations were found between fathers’ methylation at CpG M1 and children’s methylation at CpG M6. Linear regressions showed that mothers and fathers’ Global-Severity-Index predicted children’s methylation at CpG sites M2, M3 and M6, whereas fathers’ Global-Severity-Index predicted children’s methylation at CpG sites, particularly M1, M2 and M6. Moreover, offspring methylation of DAT at CpG M2 predicted Somatic Complaint, Internalizing and Attention Problems; methylation of DAT at CpG M6 predicted Withdraw. Conclusion: This study may have important clinical implication for the prevention and treatment of emotional-behavioral difficulties in children, as it adds to previous knowledge about the role of genetic and environmental factors in predicting psychopathological symptoms within non-clinical populations.